The Evolution of Philosophical Interpretation in Islam: From Classical to Modern - Haikal, Reyazul Jinan; Firdaus, Zhilal Fajar (Jurnal Iman dan Spiritualitas, 2024)
This research examines the evolution of philosophical interpretation (tafsir falsafi) from the classical to the modern period within the context of the Islamic intellectual heritage. Philosophical interpretation, integral to the journey of Muslim scholars since the classical era, serves as a "gateway" to the progress of Islamic thought. However, the philosophical nature of this interpretation has sparked controversy and is deemed problematic from an epistemological perspective, becoming a focal point of debate among the Muslim community. The research employs a library research method, utilizing various literature sources as supporting evidence, with a primary focus on both primary and secondary data. The findings indicate that the emergence of philosophical interpretation is linked to the translation of Greek works into Arabic. Some fully reject or accept it, while others integrate it with Eastern traditions. Overall, a comprehensive interpretation fully incorporating the philosophical style has not been found; usually, this style is expressed separately through writings that do not specifically interpret the Quran. The epistemology of early-generation philosophical interpretation tends to be peripatetic, involving the use of reason in discussing aspects such as divinity, the afterlife, and scientific disciplines. Some figures or philosophers relevant to the philosophical interpretation of Quranic verses include al-Kindi, al-Farabi, the Ikhwan al-Shafa order, and Ibn Sina.